THE INFLUENCE OF SCHOOL ENVIRONMENT AND LEARNING INTEREST ON LEARNING OUTCOMES (Case Study of Class X, XI and XII Students of SMA N 1 Tondano) - Listriyanti Palangda; Sjeddie Rianne Watung (J-Shelves of Indragiri (JSI), 2023)
The Influence of the School Environment and Interest in Learning on Student Learning Outcomes. The aims of this research are; 1) To determine the influence of the school environment on student learning outcomes; 2) To determine the influence of learning interest on student learning outcomes; 3) To determine the influence of the school environment and interest in learning on student learning outcomes. This research is quantitative research. The population in this study was 160 people and the sample was 40 people. The data collection techniques used in this research were questionnaires, interviews and documentation. The instrument test in this research used validity and reliability tests. Of the 15 statements for variable X1 and 15 statements for X2 given to respondents, all were declared valid and both variables were reliable. The hypothesis test used in this research is; 1) Hypotheses 1 and 2 use simple regression, simple correlation, t test and determinant coefficient; 2) Hypothesis 3 uses multiple regression, multiple correlation, F test and determinant coefficient. The results of data analysis state that; 1) There is an influence of the school environment on student learning outcomes by 74%; 2) There is an influence of the school environment and interest in learning on student learning outcomes by 66%; 3) There is an influence of the school environment and interest in learning on student learning outcomes by 78%.